Improving farm households’ economic status to address food security in Ghana: The role of participation in nonfarm activities - Eli Andrew Akosikumah; Hamdiyah Alhassan; Paul Adjei Kwakwa (Heliyon)
Understanding highly pragmatic ways of improving the quality of life of farming households by way of ensuring food security among these households has been a topical issue among many researchers. Closely linked to this technique is the participation in nonfarm activities. For a farming household, participation in such activities serves as a hedge against the risk associated with farming and by far a potential for addressing food insecurity. This study assesses the impact of participation in formal and informal nonfarm activities on household food security in Ghana using data from the Ghana Living Standard Survey 7 (GLSS 7). Multinomial Endogenous Treatment Effect was used to estimate the determinants of households' decision to engage in nonfarm activities and household food security. PSM was further used to evaluate the impact of participation in nonfarm activities on household food security. Overall, the study documents that participation in formal and informal nonfarm activities increases per capita consumption expenditure by 10 % and 9.7 % respectively. Nonfarm participation is a sure means of reducing household food insecurity shocks and improving household wellbeing. Policymakers in Ghana should therefore pay attention to nonfarm activities as a means of improving households’ welfare.